Тrends In Creative Neologization In The Language Of Modern Science (Czech Journal of Multidisciplinary Innovations, 2023)
This article analyzes the content of trends in creative neologization in the language of modern science, the issues of word-formation practice in the modern science language are considered. The trend of neologization in post-non-classical sciences is analyzed. The features of the author's neologization in science are revealed. It is noted that the author's neologization is the main way of linguistic-semiotic expression of new properties, aspects and characteristics of the object under study. As an illustration, work on neologization in such areas of post-non-classical sciences as the theory of virtuality and synergetics is considered